Mechanical Properties of Recycled High-Density Polyethylene, Rice Husk Ash, and Fly Ash Composite Mixture - Omair, Nasir; Intan Syaqirah, Mohd Zulkifli (INTI International University, 2022)
In today’s world, plastic has become a global environmental issue that needs to be addressed properly. Most of the plastic waste stems from two sources: low-density and high-density polyethylene (HDPE). HDPE has higher mechanical properties in terms of strength, rigidity, and melting point compared to LDPE. As for rice husk ash, it become abundant as a waste material in all rice producing countries. Rice husks ash (RHA) when burnt, releases particulates which are nanometers in size and can decrease air quality but more importantly can cause breathing and eye problems for humans and animals alike. Thus, the increasing interest from researchers using fillers in polymer composites has explored the potential usage of such materials. The objective of the research is to determine the mechanical properties of composite material made from high-density polyethylene (HDPE), rice husk ash (RHA) and fly ash (FA) at different composition ratio. The HDPE, RHA and FA granule is mixed according to different ratio using 3D rotary mixer and then place onto hot press machine to obtain desired shape for the mechanical testing. Four (4) types of composite were tested in this study which were: (i) 100% HDPE, 0% RHA, 0% FA (ii) 90% HDPE, 5% RHA, 5% FA, (iii) 80% HDPE, 10% RHA, 10% FA, and (iv) 70% HDPE, 15% RHA, 15% FA. The results showed that for sample 1, 2, 3 and 4; the maximum stress of 10.506 kN, 8.569 kN, 7.578 kN and 7.485 kN were observed.